Pengembangan Website UMKM untuk Meningkatkan Visibilitas di Kelurahan Karanganyar Kota Pasuruan - Ilmiyatur Rosidah; Galang Febriansyah; Maria Lordes Ukat; Novi Hidayatul Fitriyah; Tarisya Chairana Mahiira; Varizky Toriq Habibur Rohman (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service article focuses on developing a website to increase the visibility of UMKM in Karanganyar Village, Pasuruan City. Using the Participatory Action Research (PAR) method, this activity involves observations and interviews with UMKM actors to understand their needs and challenges. The development process began by redesigning the appearance and features of the website to be more user-friendly and informative, which was then integrated with the profiles of UMKM, that had not yet been registered. As a result, several UMKM, such as Permata Bread, Fish Crackers, Pecel Rice, Lele Dimsum, Motor Parts, Dumpling Noodles, Tamarind Turmeric and Bonagung Herbal Medicine, Chicken Nuggets, Macrame Glaze, Petis Tambar, and Es Agogo, were successfully added to the website. This increased visibility allows UMKM to reach a wider market, both local and international. The social impact of this development includes an increase in the number of customers and greater business opportunities for UMKM. This article concludes that website development carried out in a participatory manner can be an effective tool in empowering local UMKM, as well as encouraging economic growth and community welfare in the digital era